Dietary intake of polish organic and conventional fruit growers and their life partners – a pilot study - Dobrowolski, Hubert; Szumigaj, Bartosz; Włodarek, Dariusz; Kazimierczak, Renata; Obidzińska, Justyna; Rembiałkowska, Ewa (Frontiers in Public Health, 2024)
Diet is one of the elements that contribute to health and quality of life. There are significant discrepancies between the diets of people living in different regions, with different beliefs, or with different approaches to sustainability and ecology. There is a lack of research on dietary intake among organic and conventional fruit growers. The aim of our study was to examine the diets of orchardists and their immediate life partners in terms of meeting energy requirements, nutrient intake and fulfilment of dietary recommendations in this group. Fifty-three participants (28 in the organic group and 25 in the conventional group) took part in the study. Dietary data were obtained using the 3-day dietary record. Body mass and height were measured and BMI was calculated. Physical activity was estimated using a questionnaire method. The study group was aged 44±8 years, with a body weight of 84±16 kg and a height of 172±9 cm. The mean BMI was 28±4 kg/m 2 . Mean energy intake with diet was 2170±606 kcal/day with needs of 3002 (1991-5144) kcal/day. A significant proportion of the study group did not fulfil their calcium and vitamin D requirements. In addition, a significant proportion of the conventional fruit growers did not cover their needs for potassium, magnesium and vitamins: E, C and folate. Both groups had too high an intake of cholesterol and saturated fatty acids, and too low an intake of polyunsaturated fatty acids. In conclusion, the orchardists' diets mostly provided adequate amounts of nutrients, with inadequate intakes of calcium, vitamin D, cholesterol and fatty acids. The diets of organic fruit growers were significantly richer in selected nutrients.